Genetic diversity and molecular differentiation among Javanese Selaginella revealed by SSR and ISSR markers - AHMAD DWI SETYAWAN; JATNA SUPRIATNA; D. DARNAEDI; ROKHMATULOH ROKHMATULOH; SUTARNO SUTARNO; SUGIYARTO SUGIYARTO; SUNARTO SUNARTO; YULITA KUSUMADEWI (Society for Indonesian Biodiversity, 2026)
Abstract. Setyawan AD, Supriatna J, Darnaedi D, Rokhmatuloh, Sutarno, Sugiyarto, Sunarto, Kusumadewi Y. 2026. Genetic diversity and molecular differentiation among Javanese Selaginella revealed by SSR and ISSR markers. Biodiversitas 27 (5): d270520. https://doi.org/10.13057/biodiv/d270520. Selaginella is a highly diverse lycophyte genus in tropical Asia, yet molecular information for Indonesian taxa remains limited, particularly for evaluating species differentiation across geographically separated populations. This study assessed genetic diversity and molecular relationships among 32 Selaginella accessions representing eight recognized species and three unidentified taxonomic entities, collected mainly from Java, Indonesia, with additional materials from Bali, Lombok, and Papua. Genetic variation was analyzed using four SSR primers and five ISSR primers, which together generated 122 scorable loci, all of them polymorphic. SSR markers produced 43 loci, whereas ISSR markers generated 79 loci and contributed higher discriminatory power through greater polymorphism information content, resolving power, and marker index. Genetic similarity coefficients ranged from 0.42 to 0.93, indicating moderate to high molecular affinity among accessions. Both UPGMA clustering and principal component analysis consistently separated the major taxa, although widespread species such as S. plana and S. involvens showed moderate internal dispersion across accessions from different localities. AMOVA revealed that 80.1% of molecular variation occurred within species and 19.9% among species, with significant species-level differentiation (PhiPT = 0.199; P = 0.001). Nei's genetic distance revealed moderate molecular affinity among most Javanese taxa, whereas the Lombok and Papuan accessions occupied more divergent molecular positions. Geographic origin had little influence on the overall molecular structure, suggesting that species identity was the primary determinant of genetic differentiation. These findings demonstrate that combining SSR and ISSR markers provides a reliable molecular framework for refining taxonomy and supporting future conservation efforts for tropical Selaginella in Indonesia.